Between Ideals and Reality: A Critical Discourse Analysis of Nigeria’s Fundamental Objectives and Directive Principles of State Policy - Taiwo Joshua AJENIFARI; Samuel Adebayo OMOTUNDE (ABUAD Journal of the Humanities-AGIDIGBO)
The Fundamental Objectives and Directive Principles of State Policy of nations may not be legally enforceable, they are foundational to the vision of governance in any constitutional democracy. They provide normative standards for government action, inspire public confidence, and ensure that the machinery of the state functions in a way that benefits all citizens equitably and promotes nation-building and sustainable development. The study employs Critical Discourse Analysis (CDA) to interrogate the Fundamental Objectives and Directive Principles of State Policy (FODPSP) as outlined in Chapter II of the 1999 Constitution of the Federal Republic of Nigeria. It examines the ideological constructs embedded within these constitutional provisions and their intersection with the enduring debates that shape Nigerian nationhood. By critically engaging with some of the salient issues that have hitherto been constantly featuring in our national debates overtime, such issues as state policing, resource control, restructuring, regionalism, tax reform, local government autonomy, federalism and federal character, sharing formulas, and other socio-political and economic dilemmas, the study highlights the dissonance between the constitutional ideals and the socio-political realities of the Nigerian state. The analysis reveals how competing narratives, counter-arguments, and alternatives perpetuate the struggles to achieve equity, justice, and cohesion in governance. This work contributes to the ongoing discourse on the viability of the Nigerian state, offering insights into the interplay between policy frameworks and the realities of the Nigerian pluralistic society.